Pengaruh Teknik Journaling Dalam Layanan Konseling Kelompok Terhadap Career Decision Making Siswa - Putri Cahyani Pernandes; Mahdum; Isnaria Rizky Hayati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This ponder points to decide the level of students’ Career Choice Making some time recently and after the usage of journaling procedures in gather counseling administrations, to distinguish whether there's a critical distinction in Career Choice Making levels some time recently and after the intercession, and to get it the impact of the journaling procedure in gather counseling administrations on students’ Career Choice Making.This inquire about is quantitative in nature and employments an exploratory approach, particularly a pre-experimental plan. The investigate plan utilized is the One Bunch Pretest-Posttest Plan. The factual strategy utilized is non-parametric measurements, with information examination performed utilizing the Wilcoxon test through SPSS form 26. Based on the comes about of the Wilcoxon test, the Asymp. Sig (2-tailed) esteem is 0.043 < α 0.05, showing that Ha is acknowledged and Ho is rejected. This implies there's a significant distinction within the level of Career Choice Making some time recently and after the journaling strategy was connected in gather counseling services.Based on the N-Gain normalization test, the normal pretest score was 80.6 and the posttest score was 120.4, showing an advancement in students' Career Choice Making after the journaling method was actualized. The N-Gain esteem gotten was 0.45, which falls into the medium category, proposing that the journaling method in bunch counseling administrations incorporates a direct impact on moving forward students' Career Choice Making